DETEKSI WAJAH DENGAN METODE HAAR CASCADE MENGGUNAKAN OPENCV (FACE DETECTION WITH HAAR CASCADE METHOD USING OPENCV) - Rochmawati, Dwi Robiul (LPPM Politeknik Pajajaran ICB Bandung, 2024)
Abstract Face detection is one of the most researched topics in the field of computer vision and digital image processing. The Haar Cascade method is one method that is often used to detect faces in an image or video. This method uses Haar features to identify faces by comparing them with existing faces in the database. This research aims to implement the Haar Cascade method to detect faces using the OpenCV library. The stages include image acquisition, image processing, face detection using Haar Cascade, and evaluation of detection results. The results show that the Haar Cascade method can detect faces quite well in various lighting conditions and viewing angles. Keywords: Face Detection; Haar Cascade; OpenCV